2013
DOI: 10.1215/01636545-2210617
|View full text |Cite
|
Sign up to set email alerts
|

Xenophobia in Action

Abstract: This article investigates the use of online communication and social media in connection with the recently emerged right-wing, xenophobic movement in contemporary Japan. Since the early 2000s there has been a surge in xenophobic and racist discourse on the Internet, tied to numerous attacks on Koreans and other ethnic minorities in Japan. The result is that a new nationalist and xenophobic movement, generally referred to as the Action Conservative Movement, has emerged in Japan. Based on participant observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Although future research is necessary regarding the extent to which the number of retweets themselves represent the information spreading power of Twitter, our data suggests that it is possible that the majority of information on Twitter is being supplied by very few sources. These findings are comparable to past research results dealing with tweets not related to radiation, such as hate speech targeting foreigners in Japan [ 34 ]. Twitter is a social media platform with a high degree of free interaction between individual accounts, but in terms of information spreading, retweets account for half of the total.…”
Section: Discussionsupporting
confidence: 89%
“…Although future research is necessary regarding the extent to which the number of retweets themselves represent the information spreading power of Twitter, our data suggests that it is possible that the majority of information on Twitter is being supplied by very few sources. These findings are comparable to past research results dealing with tweets not related to radiation, such as hate speech targeting foreigners in Japan [ 34 ]. Twitter is a social media platform with a high degree of free interaction between individual accounts, but in terms of information spreading, retweets account for half of the total.…”
Section: Discussionsupporting
confidence: 89%
“…Islamophobia has not been explicit in Japan, but the rise of xenophobic movements by ultra-conservative groups in Japan since the 2000s has been identified in academic literature (Yamaguchi 2013;Shibuichi 2015). While these movements mainly target ethnic Koreans or Chinese, one group named Han Gurōbarizumu Kokusai Hoshu Rengō, or Anti-Globalism International Conservative Alliance (反グローバリズム国際保守連合; hereafter, AICA), started to target Muslims from around 2014.…”
Section: Displays Of Anti-islamic Sentiment In Xenophobic Movements Imentioning
confidence: 99%
“…Second, so-called 'hate speech' against non-Japanese in Japan has been identified as a serious social problem. Since around 2000, xenophobic discourses have emerged on the internet and, since the middle of the 2000s, ultra-conservative groups such as Kōdō-suru Hoshu Undō (行動する保守運動; 'Action Conservative Movement') have started to hold rallies verbally attacking foreign residents (Yamaguchi 2013). The targets of these movements are ethnic Korean or Chinese residents in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies conducted in similar situations of political polarization in other countries (Weimann, 2015) indicate that adolescents are more susceptible and vulnerable to extremist content. In studies conducted on Islamic radicalization (Salem et al, 2008;Yamaguchi, 2013), it was revealed that social networking platforms allow radical voices to engender "hypermedia seduction" via visual motifs and content rich with themes of graphic violence. When young individuals who have experienced situations of polarization participate in this hypermedia reality, the blatancy of the visual cues and vivid images invokes in them strong emotional and psychological responses as well as violent reactions.…”
Section: Young People's Experiences Of Political Polarization and Radmentioning
confidence: 99%